Production of Alginate Oligosaccharides (AOS) as Prebiotic Ingredients through by Alginate lyase enzyme - Fahriza Sri Afni; Sri Purwaningsih; Mala Nurilmala; Rosmawati Peranginangin (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
Prebiotics is indigestible foods that can not be digested but can stimulate the growth and activity of bacteria in the digestive tract effecting human health. Alginate oligosaccharides (AOS) can be used as a source of prebiotic. That compounds can be produced enzymatically by cutting long chain alginates using alginate lyase. The aim of this study was to produce alginate lyase enzyme then producing Alginate oligosaccharides (AOS) as a prebiotic ingredients. The alginate lyase enzyme can be produced from Bacillus megaterium bacteria using a discontinuous fermentor. The enzyme was optimum temperature of 45°C and an optimum pH of 7.0. Alginate oligosaccharides production was performed with the addition of different enzyme concentrations 25, 50, 75, and 100 U. The result of the addition of enzyme (25, 50,75 U) showed that the value of polymerization degrees (DP) were between 4-5. However, the addition of enzyme (100 U) was in the range of DP 3-4. Bacterial probiotic growth test results of Bifidobacteria and Lactobacillus showed that 1% added AOS media were able to increase the growth of probiotic bacteria compared to themedia without addition of AOS. The addition Alginate lyase activity of 50 U in AOS production is the best treatment of both probiotic bacteria.